Paylater Mindset: The Shift in Gen Z's Thinking Towards Debt from a Sharia Perspective - Rizaldy Alpiansyah; Isrun Abdurahman; Irfan Alkhotiri; Miftah Wangsadanureja; Dzulfikri (Sekolah Tinggi Agama Islam Minhajul Haq, 2026)
Digital disruption in the modern economic landscape has given birth to financial technology (fintech) instruments that radically change the consumption patterns and financial governance of society globally and nationally. One of the most dominating innovations that has sparked sharp discourse is the Buy Now, Pay Later (BNPL) service, more popularly known as paylater. Generation Z (Gen Z) and Millennials are recorded as the largest demographic of users in this service ecosystem, where the total outstanding paylater debt in Indonesia reached an aggregate figure of Rp29.59 trillion in April 2025, with a Non-Performing Loan (NPL) ratio that continues to creep up. This scientific report presents a comprehensive, in-depth, and nuanced analysis of the fundamental shift in Generation Z's mindset towards the concept of debt due to paylater penetration, evaluated strictly through the lens of Islamic economics, Fiqh Muamalah, and Maqashid Sharia. Through a synthesis of empirical data from the Financial Services Authority (OJK), behavioral economics literature, and fatwas from the National Sharia Board of the Indonesian Ulema Council (DSN-MUI), this research identifies an acute sociological shift: debt, which in Islamic tradition is inherently viewed as an emergency instrument based on mutual assistance (tabarru'), is now commodified into a lifestyle based on instant gratification and a